Discussion on IMS Network Architecture Based on P2P Content Switching - Chuanfen Feng (Dianxin kexue)
A kind of IMS network architecture based on P2P content switching was proposed by investigating 3GPP and TISPAN standards. Three kinds of applications and relevant deployment recommendations were also given based on the network architecture, which provided a better reference for realizing the streaming media service and controlling on P2P service based on IMS network.